Short Communication. Effect of the health status and geographical origin on the cork production characteristics of Western Algeria cork oak stands - Dahane, B.; Bouhraoua, R. T.; Garcia de Ceca, J. L.; Gonzalez-Adrados, J. R. (Forest Systems, 2013)
Aim of study: To analyze the effect of health status on cork production, analyzing if this influence is uniform or is affected by site conditions. Area of study: Two Western Algerian cork tree forests have been studied: M’Sila located in the coastal plains under semiarid climate, and Zarieffet, located in the mountainous interior under sub-humid climate. Material and Methods: 40 trees were selected in each forest and classified according to their health status as healthy, weakened, or decaying. A sample of cork from each tree has been obtained to measure the key variables related to cork production. A two-way ANOVA was performed considering two factors: site and health status. Main results: Quercus suber L. productivity is affected by the vitality of trees in the same way in both sources, showing values between 5.96 ± 7.1 kg • m-2 (coast, weakened trees) and 8.13 ± 0.45 kg • m-2 (mountain, healthy trees). The health status also affects the number and area of pores, especially in the cork oak groves of the coast, where the coefficient of porosity ranges from 3.79 ± 0.84% (healthy trees) to 8.11 ± 1.91% (decaying trees). The variables where the site has presented a stronger effect are those related to the amount of cork produced by the phellogen (density -kg·l-1, p<0.000- and productivity -kg·m-2, p=0.001-), and pore density (1·cm-2, p=0.001). Scrap thickness (mm) and porosity (%) show a smaller effect although still representative (p=0.041 and 0.038 respectively). Porosity and pore density show interaction site*health status. They all have higher values in the mountain (Zarieffet) than in the coast (M’Sila). The effect of tree vitality on the formation of pores in the cork oak phellogen is lower in the mountain than in the coast. No significant effects were found for any of the two factors neither on the annual growth rate nor on the thickness of the cork. Research highlights: Results lead to the conclusion that the effect of health status on traumatic phellogen formation and activity is clear but not uniform. Further studies are necessary for a deeper understanding of the effect of stress situations on pore formation and characteristics. Keywords: mean annual growth; density; productivity; porosity; decay